Enhancing pigment production by a chromogenic bacterium (Exiguobacterium aurantiacum) using tomato waste extract: A statistical approach - Birhanu Zeleke; Diriba Muleta; Hunduma Dinka; Dereje Tsegaye; Jemal Hassen (PLoS ONE, 2025)
There is a high demand for microbial pigments as a promising alternative for synthetic pigments, primarily for safety and economic reasons. This study aimed at the optimization of yellowish-orange pigment production by Exiguobacterium aurantiacum using agro-waste extracts as a growth substrate. Air samples were collected using the depositional method. Pure cultures of pigment producing bacteria were isolated by subsequent culturing on fresh nutrient agar medium. The potent isolate was identified using MALDI-TOF technique. Screening of culture conditions was done via Plackett-Burman design that highlighted culture agitation rate, initial medium pH, and yeast extract concentration as the most significant variables ( p < 0.0001) in influencing pigment production with further optimization step using response surface methodology. Among the tested agro-waste decoctions, tomato waste extract was selected for fermentation due to higher optical density of the isolate when cultivated in it compared to the other agro-waste extracts. Under optimized conditions, 0.96 g/L of pigment was extracted from 4.73 g/L of culture biomass, representing a 1.6-fold increase compared to un-optimized conditions. Spectroscopic and chromatographic analyses confirmed the presence of various functional groups, with carotenoids identified as the primary compounds responsible for the yellowish-orange pigmentation. These findings demonstrate the feasibility of enhancing bacterial pigment production using agro-waste substrates, highlighting its potential for large-scale industrial applications.